ORGANIZATION OF SCIENTIFIC AND RESEARCH ACTIVITIES OF PUPILS IN THE PROCESS OF STUDYING ORGANIC CHEMISTRY IN SCHOOLS - Горинюк, Ольга; Барус, Маріанна; Булига, Олександра; Скрипська, Ольга (Modern engineering and innovative technologies, 2023)
The manuscript describes the need to find a creative approach to teaching chemistry at school. It is important to find optimal conditions for children’s interest in learning, to increase their mental activity, encourage creativity, to achieve not only me